The modernized and higher technology agriculture of Malaysia: development of livestock industry - Ismail, N.; Mohamed Yusuff, M.K. (2009)
The Ministry of Agriculture is responsible for the modernization of the food subsector and most of the programs focused on training, marketing, credit, skills development and dissemination of knowledge on modern agriculture to farmers, as well as programs to develop entrepreneur farmers in the agro-based industries. Agriculture can be schematically identified into the modernized and traditional agriculture whereby the former is characterized by agricultural techniques of production pervaded by industrial or modernized elements and values. Types of farms, both modernized and traditional, are extremely diversified and they are characterized from several local styles of farming. Technology for agricultural development is focusing on intensifying the use of existing conventional technologies as well as prospecting and developing the potentials and applications of new and emerging technologies. Initiatives were pursued in the development of indigenous technologies as well as blending the conventional technologies with frontier technologies. This is to harness the considerable benefits that exist in their utilization while retaining some of the stronger characteristics of the traditional techniques to achieve higher productivity and quality and increase competitiveness of the sector. Biotechnology application is one of the best means to accelerate the development of modern agriculture. The thrust is to intensify Research & Development and HRD program to build pool of world class researchers and technical personnel. Government has given provision of new and additional funding for research facilities, incubation centers and designation of research universities to give equal emphasize in teaching and research. Furthermore, it is intensified joint venture program with public sectors to commercialize research finding and innovations Outline of traditional and modernized agriculture as well as the government strategies to improve the livestock industry in Malaysia is described. Examples on the application of modern technology for livestock improvement and to increase farmer’s involvement and income will be presented.